The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.3109/02841869309096138
|View full text |Cite
|
Sign up to set email alerts
|

Immunotargeting with Monoclonal Cytokeratin 8 Antibodies of Human Urothelial Cancer Transplanted to Nude Mice

Abstract: The possibility of using cytokeratin antibodies for the radioimmunolocalization of urinary bladder cancer was studied. A monoclonal murine IgG antibody was raised against cytokeratin 8 and labelled with iodine-125; normal murine IgG was used for control purposes. The urothelial cancer cell line RT4 was transplanted into immunodeficient nude mice. The anti-cytokeratin 8 antibody was administered intraperitoneally and its uptake in the tumour and other organs was analyzed with a computerized gamma camera. Optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…The synthesis of cytokeratins is usually maintained during malignant transformation, and this feature serves as one of the hallmarks of epithelium-derived tumours (Tseng et al, 1982), including tumours of the urinary tract (Moll et al, 1982(Moll et al, , 1988Letocha et al, 1993;Cilento et al, 1994). Cytokeratin 7 has been considered a urothelial marker (Cilento et al, 1994), while cytokeratin 13 is a squamous cell marker with trace amounts of component 13 expressed in basal and intermediate cells of human urothelium and low-grade TCC (Moll et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of cytokeratins is usually maintained during malignant transformation, and this feature serves as one of the hallmarks of epithelium-derived tumours (Tseng et al, 1982), including tumours of the urinary tract (Moll et al, 1982(Moll et al, , 1988Letocha et al, 1993;Cilento et al, 1994). Cytokeratin 7 has been considered a urothelial marker (Cilento et al, 1994), while cytokeratin 13 is a squamous cell marker with trace amounts of component 13 expressed in basal and intermediate cells of human urothelium and low-grade TCC (Moll et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of some CKs, including CK8, CK18, and CK19, has been reported in several cancers and is believed to be involved in tumor progression based on several studies (Letocha et al 1993, Silen et al 1994, Fujita et al 1999, Fukunaga et al 2002, Cimpean et al 2008, Kabukcuoglu et al 2010. Another study reported the high expression of pan-CK, CK8, and CK19 in malignant thyroid tumors (Schroder et al 1996).…”
Section: Endocrine-related Cancermentioning
confidence: 99%